Archetype for implementing Rapid Cycle Genomic Selection (RCGS) in CGIAR-NARES-SME breeding network pipelines: Examples for pure line crops; RTB crops and hybrid crops - CGIAR Initiative on Accelerated Breeding; International Maize and Wheat Improvement Center (CGIAR, 2024)
Accelerated Breeding Initiative’s aim is to develop a continuous stream of climate-resilient, preferred, inclusive, high-yielding, and nutritious varieties, against the present-day global challenges such as climate change and environmental degradation. We are committed to increasing genetic gains in farmer’s fields by developing and availing to seed systems new varieties that perform well under farmer conditions and have clear advantages in essential traits that can be recognized by farmers and end-users in order to incentivise the farmers to adopt the new varieties in lieu of their familiar varieties, and to do so at a pace that matches the increasingly erratic growing conditions. The rapid cycle genomic selection (RCGS) archetype seeks to enable selection and recycling of new parents as fast as possible – preferably two-to-three-year cycles, using data that is accurately representing the target population of environments (TPE) in which the future potential varieties will grow. This will ensure that breeding populations are continuously improved to provide high-value alleles and haplotypes for adaptation to biotic and abiotic stresses, and high-value parents from which superior products are identified and released as new varieties. To achieve this we need to: i) Take advantage of the BRS-procured genotyping services with mid-density marker panels that can estimate genomic relationships and marker effects; ii) Deploy new testing strategies that sample the TPE better, using relatively similar resources, e.g. by use of sparse testing where alleles are replicated across locations in the TPE without physical replications or with partial replications, and using the family structure and genomic relationships to provide connectivity, as well as the additional use of managed stress trials to mimic different environments; iii) Build and leverage on efficient CGIAR-NARES-SME breeding networks to scale up testing sites at Early Testing 1 and develop innovative ways for resource reallocation between Early Testing and later stages of testing; iv) Recycle new parents for population improvement faster using the improved accuracy from better testing strategies. In this document we: • Articulate a value proposition for working as a breeding network to CGIAR-NARESSME partners. • Provide clear steps on how to redesign existing pipelines to optimally implement a rapid cycle genomic selection scheme, with example breeding schemes in pure line crops, roots, tubers and bananas (RTB), and hybrid crops. • We identify the support and services needed by the CGIAR-NARES-SME breeding networks to implement this archetype.